Politik kebijakan pendidikan di Indonesia : peran tokoh-tokoh Islam dalam penyusunan uu no.2/1989 - Tedjasudhana, Lilian D (INIS, 2004)
judul asli: Politics of educational policy production in Indonesia, A case study of the roles of muslim leaders in the establishment of the number 2 act of 1989